Cytochalasin B: Effects upon Microfilaments Involved in Morphogenesis of Estrogen-Induced Glands of Oviduct - Wrenn, Joan T. (1970)
The administration of estrogen to immature chicks induces formation of tubular glands and differentiation of cells in the oviduct. As glands begin to form, organized bundles of 40-50 Å filaments appear at the luminal end of the cells. These structures are not present in uninduced oviducts. Cytochalasin treatment of oviducts early in gland formation results in the disappearance of young glands already present and the inhibition of new gland formation. Furthermore, organized microfilaments are no longer present. When the oviducts are washed free of cytochalasin, however, organized bundles of microfilaments reappear. The correlations between the presence of filaments and formation and glands suggest that filaments are important agents in morphogenesis, presumably because of contractile properties which generate changes in cell shape and, consequently, tissue shape.